Bourdieu’s social class and the processing of political choices in Indonesia - Rahman, M. Fajrul; Ilya Revianti (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article analyses the new model of social class in Indonesia based on the concept of capital of Pierre Bourdieu’s genetic structuralism theory, with the processing of political choice based on the Elaboration Likelihood Model of Richard Petty & John Cacioppo. The concepts of cultural capital, social capital and economic capital from Bourdieu are used to identify the new models of social classes in Indonesia’s historical context. This research on voter behaviour uses a mixture of quantitative and qualitative methods and resulted in: 1. finding four social classes in the contemporary Indonesian society, namely the elite class, the professional middle class, the traditional middle class and the marhaen class; 2. finding out that key informants from the elite and professional middle classes process political choice information through the central route, while the traditional middle class and the marhaen class process political choice information through the peripheral route.